THE PILGRIMAGE TRADITION AS AN ECONOMIC SOURCE FOR THE COMMUNITY AROUND THE SACRED TOMB - Subekti, Priyo; Nugraha, Aat Ruchiat; Sjoraida, Diah Fatma (Jurnal Penelitian Manajemen Terapan (PENATARAN), 2024)
In Indonesia, the activities of coming to the graves of ancestors of the Prophet are prevalent. It encompasses the trifecta of economy, culture and religion. Grave of Sheikh Abdul Muhyi in Pamijahan, Tasikmalaya is an instance of where such religious activities can be transformed into profit by the community. With the context of women and tomb visiting, this research aims to identify the nexus of spirituality, culture, and economic development through this practice. The study was qualitative and descriptive in nature. The researchers were purposefully engaged to select samples of three groups: pilgrims, local business operators, and tomb caretakers. A detailed questionnaire was developed for in-depth interviews, as well as observational techniques. Thematic analysis was employed as a qualitative data analysis approach. Results indicate that there is considerable economic activity stemming from the activities of pilgrimage. More than 230 traders depend on these centuries old traditions as they prepare food, gift articles as well as offer guiding and accommodation services. Islamic trading principles bring added value to such interactions where trust and justice prevail. It contributes in terms of revenue generation, growth of the informal sector and avenues for cultural preservation. As consequence of the migration streams for economic reasons local development through remittances and increased economic activities is also achieved. The pilgrimage tradition practised at Sheikh Abdul Muhyi’s Tomb clearly illustrates the juxtaposition of spirituality and economics and therefore can serve as a good example for culture based community development.